Fostering Mental Health Awareness in the Academic Workplace: Supporting Campus Internationalization Through Community Well-Being - Fourianalistyawati, Endang; Akmal, Sari Zakiah; Lubis, Fauziah Hanim Dara Sutra; Navyliawati, Jasmine Reggina; Shofiyah, Salsabila; Kamila, Syafa (KnE Social Sciences, 2025)
In the context of increasing campus internationalization, maintaining robust mental health support systems is crucial for creating an environment conducive to global academic excellence. This paper presents the implementation and outcomes of a World Mental Health Day 2024 initiative at YARSI University, designed to enhance students’ and staff’s awareness of their mental health and wellbeing. The program, themed “It Is Time to Prioritize Mental Health in The Workplace,” incorporated five strategic programs: Stress Scribe Session, Mood Tracker, Affirmation Wall, Positive Affirmations and Reward Corner, and Professional Counseling Services, including peer counseling. The initiative engaged 151 participants (104 students and 47 staff members), achieving the target participation rate of 75%. The program responded to evolving needs in education by providing accessible mental health resources and creating safe spaces for emotional expression. The peer counseling component was particularly significant in building support systems that enhance community wellbeing. This initiative demonstrates how universities can strategically address mental health needs while building a resilient academic community. Such mental health awareness programs can also contribute to strengthening the psychological preparedness needed for future international academic engagement. The program’s success suggests that integrated mental health initiatives are fundamental to supporting campus development efforts and ensuring the readiness of all academic community members for future global engagement.